“Swipe & slice”: decoding digital struggles with non-suicidal self-injuries among youngsters - Orsolini, Laura; Reina, Salvatore; Longo, Giulio; Volpe, Umberto (Frontiers in Psychiatry, 2024)
Nonsuicidal-self-injury (NSSI)-related content recently emerged on social networking sites (SNS), despite its relationship with NSSI conducts is still unclear. Hence, the current population-based crosssectional study investigated the interplay between SNS use, NSSI content engagement, risky social media challenges (RSMCs), in a sample of 404 young adults (aged 18-24), focusing on the influence of problematic social media use (PSMU) and fear of missing out (FoMO). Around 51.5% of the sample was engaged in NSSI-related contents on SNS, being mostly females (p<0.001), younger (p=0.005), transgender people and non-binary people (p=0.030) and those who displayed higher PSMU (p<0.001) or FoMO (p=0.031). Around 66.2% of the sample currently practice NSSIs, predominantly among females (p<0.001), those using BeReal (p=0.012), actively looking for NSSI-related contents on SNS (p<0.001) to be part of a group (p=0.0025) or learn how to practice NSSI (p=0.025). PSMU (p<0.001) and FoMO (p<0.001) emerged as significant predictors of NSSI content engagement, particularly among active seekers. NSSI conducts were significantly predicted by FoMO (p<0.001) and Snapchat (p=0.044), while negatively predicted by male sex (p<0.001), higher educational level (p=0.019) and age at which NSSI-related contents were firstly looked for (p=0.028). These findings underline the need to implement preventive policies and targeted interventions to monitor NSSI-related contents on SNS, the impact of PSMU and FoMO on NSSI, particularly among youngsters.